Effects of English learning gains among college students on learning engagement: subjective wellbeing as a mediating variable and pro-environmental behavior as a moderating variable - Zhang, Chengli; Han, Ying; Yang, Aijun (Frontiers in Psychology, 2026)
PurposeIn today’s diverse social environment, college students often struggle to devote sufficient time to English learning, potentially affecting their academic performance, psychological wellbeing, social development, and career prospects. This study examined a moderated mediation model to explore how English learning gains influence learning engagement, with subjective wellbeing as a mediator and pro-environmental behaviors as a moderator.MethodsA total of 1,354 valid responses were collected from 1,500 students at an independent university in Shanxi Province, China. Data were analyzed using SPSS 27.0 and PROCESS 4.0, applying Pearson correlation and hierarchical linear regression analyses. The results revealed significant positive associations among pro-environmental behaviors, English learning gains, subjective wellbeing, and learning engagement.ResultsEnglish learning gains significantly predicted learning engagement, and subjective wellbeing mediated this relationship. Pro-environmental behaviors moderated the mediating pathway, strengthening the effects of both learning gains and subjective wellbeing on learning engagement.ConclusionThese findings provide empirical evidence on the mechanisms underlying college students’ English learning engagement and offer practical guidance for educational institutions to support student learning through wellbeing enhancement and pro-environmental initiatives.